Beyond the bend: The curvilinear effect of challenge stressors on work attitudes and behaviors. (June 2022) - Haldorai, Kavitha; Kim, Woo Gon; Phetvaroon, Kullada
Abstract: The purpose of this study is to investigate the curvilinear relationships between challenge stressors, service-oriented OCB, and service sabotage behavior. We further predicted that job satisfaction will nonlinearly mediate, and psychological capital will moderate, these relationships. Using a three-wave design, data was collected from 320 Thai hotel employees. Consistent with our prediction, challenge stressors had an inverted U-shaped relationship with service-oriented OCB and a U-shaped relationship with service sabotage behavior. Furthermore, job satisfaction nonlinearly mediated these relationships. Additionally, when psychological capital was low (versus high), the curvilinear relationships were more pronounced. The findings enhance the current understanding of the conditions under which different levels of challenge stressors bolster or hinder work behaviors. Theoretical and practical implications are discussed. Limitations and avenues for further research are outlined.